Extraction of ß-glucan from Oat and its Interaction with Glucose and Lipoprotein Profile - Ahmad, Asif; Anjum, Faqir Muhammad; Zahoor, Tahir; Nawaz, Haq (Pakistan Journal of Nutrition, 2009)
ß-glucan was extracted and purified from oat, at various temperature and pH levels. Response surface methodology was applied to optimize the temperature and pH for extraction of ß-glucan gum pellets. Higher temperatures and neutral pH appeared to increase the yield of gum pellet and recovery of ß-glucan in extracted gum pellets. An extraction temperature of 50°C with a pH 7 was proved effective in removal of more of the impurities from the gum pellet. All the treatments extracted higher amounts of SDF (74.11-76.85%) and TDF (86.71-91.03%) in the extracted gum pellets. However, soluble dietary fiber and total dietary fiber content of gum pellets declined with increase in pH of extrcation medium. Serum glucose, total cholesterol, triglycerides and LDL cholesterol of albino rats decline with administration of increased doses of gum pellet extracted at temperature of 50°C with a pH 7. Incorporation of this gum pellet at 5% level in feed of rats increase the HDL by 37.74% over control group of rats. The reduction in lipoprotein fraction was directly associated with presence of SDF and TDF in the gum pellets.